Um estudo de pequenas cidades:o caso de Mata - Melchiors, Celita; Bellinaso, Lisandra Maria; Zibordi, Antonio Francisco Guerreiro (Geografia Ensino & Pesquisa, 2016)
Um estudo de pequenas cidades:o caso de Mata